ANALYSIS OF TEACHER'S ACCEPTANCE OF TECHNOLOGY USES IN TEACHING IMPLEMENTATION POST COVID-19 PANDEMIC - Ardelia, Cindy; Adeline, Clarissa (Universitas Pelita Harapan, 2025)
As we enter the era of digital transformation, the integration of Information and Communication Technology (ICT) has become essential in various sectors, particularly in education. The use of ICT in the learning process is crucial and significantly enhances the quality of education. In Indonesia, however, integrating ICT into education remains a challenge, especially following the onset of the COVID-19 pandemic. Despite these challenges, this situation also presents new opportunities for digital transformation. Acceptance of technology is a key requirement for effective integration of ICT in the learning process. Therefore, this research aims to analyze the technology acceptance among teaching staff regarding the use of ICT in education following the COVID-19 pandemic. This study employs a qualitative approach using a case study method. Data was collected through in-depth, semi-structured interviews with three purposively selected informants. Data analysis was conducted using the Technology Acceptance Model, and data validity was ensured through source triangulation. The results indicate that using ICT is viewed as beneficial for supporting classroom learning and is considered easy to implement and use. Consequently, ICT integration has been accepted in post-COVID-19 education as a valuable tool for enhancing the learning experience.